Glycemic repercussions of bed bath of critically ill cancer patients: clinical trial (Research, Society and Development, 2020)
Objective: to compare the blood glucose difference of cancer patients admitted to the ICU before and after bed bath with wet wipes. Method: Uncontrolled clinical trial conducted at the Intensive Care Unit (ICU) and Post-Operative Unit (POU) of a single health service, a reference in cancer treatment in Latin America. Sample composed of 30 consecutive hospitalized cancer patients. All blood samples for blood glucose measurement were collected from invasive pressure catheters five minutes before and five minutes after bed bath with wet wipes, considering hyperglycemia values above 180 mg/dL. To compare the pre and post bath blood glucose medians, the Wilcoxon test was used with a pre-established significance level of 5%. Results: In the pre-bath moment, a median glycemia of 141 mg/dL was obtained, and in the post-bath moment, the median was 135 mg/dL. It was observed that in the post-bath moment there was a 7.05% reduction in glycemia, this drop being statistically significant (p < 0.01). Conclusion: Bed bath with the use of sanitizer and skin protector wipes performed on cancer patients admitted to clinical and surgical intensive care units significantly reduces the blood glucose of these individuals.